Vitamin C for pregnant smokers. Issue 1 (January 2015) - Oshman, Lauren
Abstract : N/A: McEvoy CT, Schilling D, Clay N, et al. Vitamin C supplementation for pregnant smoking women and pulmonary function in their newborn infants: a randomized clinical trial. JAMA . 2014; 311(20):2074–2082.